TAHAPAN PENGEMBANGAN KOLEKSI DISABILITAS DI PERPUSTAKAAN PERGURUAN TINGGI (STUDI KASUS PERPUSTAKAAN UIN SUNAN KALIJAGA YOGYAKARTA) - Riazmi Yusma Sari; Anis Masruri (Jurnal Pustaka Ilmiah, 2020)
The core process of activities in a library is to develop collections for the advancement of knowledge sources. Collection development in this research is in the library of Sunan Kalijaga State Islamic University of Yogyakarta. This study aims to determine the stages of collection development at the UIN Sunan Kalijaga Yogyakarta library, and its object, namely students with disabilities. This research uses a qualitative research method with a descriptive approach. Data collection techniques used in this study were through observation and interviews. Observations were carried out by directly jumping into the field to explore information related to the stages of collection development, and interviews were conducted with Mrs. Dra. Ida Nor’aini Hadna, M.Pd (Kobid Technical Services) and Isrowiyanti (Information Kour). Based on this research, it was concluded that the stages of collection development offered by Evans with 6 components of activities consisting of community analysis in this case the user community, selection policy, selection, procurement, weeding, and evaluation. This theory is applied in the Sunan Kalijaga UIN Yogyakarta library. Normal students and people with disabilities at UIN Sunan Kalijaga Yogyakarta have the same knowledge needs, grouped in the same class. But in this case what distinguishes it is the way to access that is done by students with disabilities with the addition of assistance through audio and visual media and others.